2017
DOI: 10.5937/str1702020n
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4 nanoparticles as additives for gamma-ray shielding: Structural and surface characterization

Abstract: Monodisperse samples of magnetite nanoparticles in the size range of 5-13nm, were prepared by solvothermal synthesis and coprecipitation method. Obtained nanoparticles were characterized by different measurement techniques: X-ray diffraction analysis, transmission electron microscopy, selected area electron diffraction measurement, and Fourier transform infra-red spectroscopy. Measurements confirmed that the utilized synthesis methods are able to produce size and shape-controlled nanoparticles of a high-qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The mean particle size of about 300 μm was determined, and it was also found that two main sizes dominate (75 and 700 μm). In general, the method of determining the mean particle size of the mixture is complex and not reliable, and it is actual wherever the problem of small particles is present [10,11].…”
Section: Separation Of Different Mixture Granulationsmentioning
confidence: 99%
“…The mean particle size of about 300 μm was determined, and it was also found that two main sizes dominate (75 and 700 μm). In general, the method of determining the mean particle size of the mixture is complex and not reliable, and it is actual wherever the problem of small particles is present [10,11].…”
Section: Separation Of Different Mixture Granulationsmentioning
confidence: 99%
“…The optical properties of the samples, absorbance and bandgap energy were obtained from UV-VIS spectroscopy. 400), (511), and (440) corresponding to JCPDS Card No.00-900-2674 [51]. These peaks are demonstrating cubic inverse spinel structure of Fe3O4 which are sharp and intense to be well crystallized structure [52].…”
mentioning
confidence: 92%